Radius and angle determination of diamond Berkovich indenter. (July 2017) - Zong, W.J.; Wu, D.; He, C.L.
Highlights: AFM and CLSM are used to determine the tip shape of diamond Berkovich indenter. A new area function that considers the effect of edge radius is established. AFM method and new area function can jointly determine the tip and edge radii. CLSM method is capable to accurately evaluate the angle parameters. Abstract: In this work, a new measurement method based on atomic force microscope (AFM) and confocal laser scanning microscope (CLSM) is proposed to determine the radius and angle parameters of diamond Berkovich indenter. In order to accurately describe the real tip shape, a comprehensive geometrical model that takes the effects of indenter edge radius and tip radius into account is established. Resultantly, a sophisticated area function is formulated to fit the AFM acquired topographies. Comparison reveals that the fitted data of indenter radius have a satisfactory consistency with the experimental results. For the determination of angle parameters, the CLSM relevant 3D topography acquisition, angle calculation and error correction methods are constructed. Experimental observations validate that the CLSM method is capable of accurately determining the angle parameters of diamond Berkovich indenter.